2013
DOI: 10.1002/jms.3194
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry imaging as a tool for surgical decision‐making

Abstract: Despite significant advances in image-guided therapy, surgeons are still too often left with uncertainty when deciding to remove tissue. This binary decision between removing and leaving tissue during surgery implies that the surgeon should be able to distinguish tumor from healthy tissue. In neurosurgery, current image-guidance approaches such as magnetic resonance imaging (MRI) combined with neuro-navigation offer a map as to where the tumor should be, but the only definitive method to characterize the tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 79 publications
0
33
0
Order By: Relevance
“…The samples from the contralateral breast were obtained from five research subjects who underwent double mastectomies. All of the samples were analyzed in negative ion mode in the m/z range of 50-1,100, meaning that the negative ions detected were predominantly lipid and metabolite species (47,51,54,56,59,60). Compared with positive ion mode, the lipid spectra obtained from negative ion mode gave more unique information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples from the contralateral breast were obtained from five research subjects who underwent double mastectomies. All of the samples were analyzed in negative ion mode in the m/z range of 50-1,100, meaning that the negative ions detected were predominantly lipid and metabolite species (47,51,54,56,59,60). Compared with positive ion mode, the lipid spectra obtained from negative ion mode gave more unique information.…”
Section: Resultsmentioning
confidence: 99%
“…lipid profiles associated with different human cancers have been investigated by DESI-MSI (55)(56)(57)(58). Moreover, the grades and subtypes of human brain tumors have been discriminated using this technique.…”
mentioning
confidence: 99%
“…We have recently shown that desorption electrospray ionization (DESI) MS is a powerful methodology for characterizing lipids within tumor specimens (3)(4)(5)(6). The intensity profile of lipids ionized from within tumors can be used for classifying tumors and for providing valuable prognostic information such as tumor subtype and grade.…”
mentioning
confidence: 99%
“…The intensity profile of lipids ionized from within tumors can be used for classifying tumors and for providing valuable prognostic information such as tumor subtype and grade. Because DESI MS is performed in ambient conditions with minimal pretreatment of the samples (7,8), there is the potential to provide diagnostic information rapidly within the operating room (4,6,9). The ability to quickly acquire such valuable diagnostic information from lipids prompted us to determine whether we could use DESI MS to detect additional molecules of diagnostic value within tumors, such as their metabolites.…”
mentioning
confidence: 99%
“…This technique has been used for characterizing molecules such as proteins, peptides, lipids, and metabolites in tissue samples (17)(18)(19)(20)(21)(22)(23)(24). Desorption electrospray ionization (DESI) coupled with MSI has already been shown to distinguish cancerous from noncancerous tissue, and studies validating its implementation in an operating room for real-time and near-real-time diagnosis have been presented (25)(26)(27)(28). Matrix assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) has also shown great promise in supporting approaches already used in clinical diagnostic practice (29)(30)(31)(32).…”
Section: Significancementioning
confidence: 99%